Serotonergic system modulation holds promise for L‐DOPA‐induced dyskinesias in hemiparkinsonian rats - Farajdokht, Fereshteh; Sadigh-Eteghad, Saeed; Majdi, Alireza; Pashazadeh, Fariba; Vatandoust, Seyyed Mehdi; Ziaee, Mojtaba; Safari, Fatemeh; Karimi, Pouran; Mahmoudi, Javad (IfADo - Leibniz Research Centre for Working Environment and Human Factors, Dortmund, 2020)
The alleged effects of serotonergic agents in alleviating levodopa-induced dyskinesias (LIDs) in parkinsonian patients are debatable. To this end, we systematically reviewed the serotonergic agents used for the treatment of LIDs in a 6-hydroxydopamine model of Parkinson’s disease in rats. We searched MEDLINE via PubMed, Embase, Google Scholar, and Proquest for entries no later than March 2018, and restricted the search to publications on serotonergic agents used for the treatment of LIDs in hemiparkinsonian rats. The initial search yielded 447 citations, of which 49 articles and one conference paper met our inclusion criteria. The results revealed ten different categories of serotonergic agents, including but not limited to 5-HT1A/BR agonists, 5-HT2AR antagonists, selective serotonin reuptake inhibitors (SSRIs), serotonin-norepinephrine reuptake inhibitor (SNRIs), and tricyclic antidepressants (TCAs), all of which improved LIDs without imposing considerable adverse effects. Although there is promising evidence regarding the role of these agents in relieving LIDs in hemiparkinsonian rats, further studies are needed for the enlightenment of hidden aspect of these molecules in terms of mechanisms and outcomes. Given this, improving the quality of the pre-clinical studies and designing appropriate clinical trials will help fill the bench-to-bedside gap.
A systematic review
EXCLI Journal;Vol. 19. 2020, pp. 268-295
Keywords: L-DOPA; Levodopa-induced dyskinesias; 6-hydroxydopamine; Rat; Serotonergic system; 610